Microspherophakia-metaphyseal dysplasia: a 'new' dominantly inherited bone dysplasia with severe eye involvement. Issue 7 (July 1990) - Verloes, A; Van Maldergem, L; de Marneffe, P; Dufier, J L; Maroteaux, P
Abstract : We report a father and son affected by a hitherto unpublished bone dysplasia with moderately severe dwarfism. On initial radiographs, thickening of the diaphyses of the long bones was striking. The small bones of the extremities were almost unaffected. With age, the metaphyseal deformation became more prominent. The epiphyses became irregular and their growth was delayed (particularly the femoral heads). The femoral neck showed an unusual 'lip' on the inner edge. Later, the stubby appearance of the long bones faded and, in adulthood, only enlarged metaphyses and deformed femoral necks persisted. The vertebrae showed moderate deformation with irregular flattening, and narrowing of the spinal canal with a shortened interpedicular distance. The eye defects consisted of high grade myopia, microspherophakia, lens coloboma, lens luxation, and retinal detachment. The name 'microspherophakia-metaphyseal dysplasia' is suggested for this probably autosomal dominant bone dysplasia.